Horror in the age of steam : tales of terror in the Victorian age of transitions - Savant, Carroll Clayton (New York, NY : Routledge, 2021)
"Faced with scientific innovation and industrial advancement, Victorians sought new ways to deal with their new moment in history. Many turned to artistic movements of the past; there were authors, however, who created new forms of storytelling, the horror story, to illustrate the terrors of an age in transition"--
OCLC-licensed vendor bibliographic record.
Keywords: English literature -- 19th century -- History and criticism; Horror tales, English -- History and criticism; Horror in literature; Psychic trauma in literature; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh